PENGARUH RISIKO-RISIKO PASAR, KREDIT, LIKUIDITAS DAN OPERASIONAL TERHADAP EARNING BANK PEMBANGUNAN DAERAH (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2016)
This research aims to determine the effect of Risks Market, Credit, Liquidity and Operational to Earnings of Regional Development Banks. Based on the analysis result obtained Partial indicate Market Risk variable (NIM) significant positive effect to Earning (ROA), Credit Risk (NPL) had no significant positive effect to Earning (ROA), Risk Liquidity (LDR) significant positive effect to Earning (ROA) and Operational Risk (BOPO) significant negative effect on Earning (ROA) in the Regional Development Banks. Then simultaneously indicate that the variables Market Risk (NIM), Credit Risk (NPL), Liquidity Risk (LDR) and Operational Risk (BOPO) significantly effects to Earning the Regional Development Banks.Keyword: Market Risk (NIM), Credit Risk (NPL), Liquidity Risk (LDR), Operational Risk (BOPO) and Earning (ROA).